Enhancing Competitiveness in the Business Sector and its Role in Supporting Economic Development: The Sultanate of Oman as A Model - Al-Sanani, Mohammed bin Salem bin Nasser; Hassan, Wan Zulkifli bin Wan; Zain , Mat Noor Mat (Journal of Ecohumanism, 2025)
Due to the remarkable technological development, the world has witnessed great interest in the areas of the business sector and competition between companies and organizations of all types and sizes. Therefore, this has a significant impact on the economic development of countries. The Sultanate of Oman is currently witnessing a huge economic and technological changes that and working to achieve the provisions of Vision 2040, which revolves around developing the local business sector to become the basic base for economic development. Therefore, this research aimed to clarify the role of the business sector in enhancing competitiveness and supporting economic development in the Sultanate of Oman. The researcher will rely on a group of previous studies that discuss and focus on the variables of the study, especially in the Sultanate of Oman. The results of previous studies found that there is a weakness in the ability of the Omani market to seize opportunities that enhance competitiveness due to the government’s control over a number of economic activities available for investment and implementation of local projects. There is also a clear gap in studies that contain the variables of the current research, so our research will be a wealth of information that will benefit other researchers and academics. The current research aims to clarify the role of the business sector in enhancing competitiveness and supporting economic development in the Sultanate of Oman. Therefore, the researcher will rely on a group of previous Arab and foreign studies that discuss the research variables to rely on valuable and rich information that supports our current research.